Literasi Pajak Sebagai Pemoderasi: Pengaruh E-Filling System Terhadap Kepatuhan Wajib Pajak UMKM di Kota Ambon - Tuhumena, Aleida Marryane; Patty, Junus Paulus (ISAS, 2025)
This study empirically examined the influence of e-filing system implementation on taxpayer compliance, specifically investigating the moderating effect of tax literacy on the relationship between e-filing system implementation and compliance among Micro, Small, and Medium Enterprises (MSMEs) in Ambon City. In collecting the data of this study, a survey questionnaire was administered to selected respondents using purposive sampling, based on specific research criteria. The primary analytical technique employed was Moderated Regression Analysis (MRA), utilizing a significance level of 0.05 (5%). The findings indicated that the implementation of the e-filing system has a significant positive influence on taxpayer compliance, as evidenced by the statistically significant t-statistic for the e-filing variable (p-value below the established significance level). Moreover, tax literacy significantly strengthened the positive influence of e-filing system implementation on taxpayer compliance. This moderation effect was evidenced by the statistically significant positive coefficient of the interaction term (Z*X) in the hypothesis testing results. Keywords: e-filing system, tax literacy, taxpayer compliance